Extraction of lineaments and faults using gravity second horizontal derivative data obtained using Fourier transform - Epuh, E. E.; Joshua, E. O. (Geofizicheskiy Zhurnal, 2018)
Linear anomalies are important in the interpretation of gravity data because they indicate some important structural features. Gravity anomalies obtained from horizontal derivatives generally reflect lineaments and faults or compositional changes which can describe structural trends of a region. This study involves the delineation of the Gongola basin structural trend based on the convolution between the Fourier kernel obtained from the second horizontal derivative (SHD) of the truncated horizontal plate model (THPM) and the gravity anomaly. The Fourier kernel for the second horizontal derivative was obtained through the application of Fourier transform over the expression of a Bouguer slab with exponential density contrast variation. The weighting density distribution is obtained through the determination of the mean depth perturbed by interfaces. The edges were identified by the closed maximum in the SHD gravity map. The results show that the region’s Bouguer gravity is characterized by elongated SE-NE negative gravity anomaly corresponding to a collapsed structure associated with a granitic intrusion beneath the region, limited by the fault systems. This was clearly evident on an isostatic residual gravity map. The horizontal gradients of the Bouguer gravity anomaly data from the basin defined the edges, lineaments and faults structures very clearly. Major and minor lineaments derived from the SHD map were transposed on the isostatic residual map. These features led to the production of the structural map of the study area. The NE-SE and E-W trending lineaments were interpreted as fault (strike-slip wrench) systems. The steep gradients evident in the gradient maps are reflection of sharp discontinuities or interfaces between basement blocks of contrasting properties, such as: fault, basement shear zones and intrusive contacts. The tectonic information brought about by the distribution of the lineaments was corroborated by the 2D gravity model of the basin. These models and fault map will complement the selection of the promising areas for detailed hydrocarbon mapping.